Учасники виконавчого провадження в Україні та їхні повноваження на сучасному етапі - Міхєєв, Михайло Володимирович (My University, 2017)
Досліджено проблеми виконавчого провадження в Україні та зміни, які виникли у зв’язку з введенням інституту приватних виконавців. Проаналізовано позитивні та негативні аспекти введення згаданого інституту. Розглянуто обсяг повноважень державних та приватних виконавців, а також їхні права. The problems of enforcement proceedings in Ukraine and the changes that have arisen in connection with the introduction of the institution of private enforcement agents are investigated. The positive and negative aspects of the introduction of the mentioned institution are analyzed. The scope of powers of state and private enforcement agents, as well as their rights, are considered.
Keywords: виконавче провадження; enforcement proceedings; державний виконавець; public servant